Involving Individuals in Health and Fitness Practices through Social Media - Ramakrishnan, D; Sunitha, D (Journal of Advanced Research in Journalism & Mass Communication, 2018)
With the influencing nature of the social media, individuals are motivated to understand the importance of health and fitness within their daily routine lifestyle. How to be fit? Social media platform Twitter is used to challenge and motivate individuals to make efforts for their own health and wellbeing within their daily activities. The paper will present the active participation of individuals from all walks of life to show how they display their communication in understanding the importance of health and fitness. The formation of influencer sets and the cascading effect of spreading social health information will be analyzed in the case study. Fit India Campaign, a successful campaign, initiated by the Hon’ble Minister of Sports and Youth Affairs, Ministry of Sports and Youth Affairs, Government of India has been chosen for the case study. The campaign was disseminated effectively online though the social networking platform Twitter to make every individual’s active participation in accepting fitness challenges and posting their response workout videos and health ideas. The paper will also focus on how the celebrities and fitness expert’s influence through social media to engage citizen in participating in the government initiative to create health and fitness awareness. The paper will submit a heterogeneous social network approach in propagating the social message to connect individuals about fitness and health practices. How to cite this article: Ramakrishnan D, Sunitha D. Involving Individuals in Health and Fitness Practices through Social Media. J Adv Res Jour Mass Comm 2018; 5(4): 164-166. DOI: https://doi.org/10.24321/2395.3810.201834